2014
DOI: 10.2139/ssrn.2523376
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity of Adults: A Survey of Correlates, Determinants, and Effects

Abstract: Die Dis cus si on Pape rs die nen einer mög lichst schnel len Ver brei tung von neue ren For schungs arbei ten des ZEW. Die Bei trä ge lie gen in allei ni ger Ver ant wor tung der Auto ren und stel len nicht not wen di ger wei se die Mei nung des ZEW dar.Dis cus si on Papers are inten ded to make results of ZEW research prompt ly avai la ble to other eco no mists in order to encou ra ge dis cus si on and sug gesti ons for revi si ons. The aut hors are sole ly respon si ble for the con tents which do not neces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 102 publications
0
10
0
1
Order By: Relevance
“… 1 See Cabane and Lechner [2014] for an extensive survey on the determinants and outcomes of physical activity during adulthood. …”
mentioning
confidence: 99%
“… 1 See Cabane and Lechner [2014] for an extensive survey on the determinants and outcomes of physical activity during adulthood. …”
mentioning
confidence: 99%
“…High school and college athletes earn more in labor markets (Barron, Ewing, and Waddell 2000;Cabane and Lechner 2014;Ewing 1998Ewing , 2007Lechner 2009;Lechner and Downward 2013;Lechner and Sari 2014;Long and Caudill 1991;McCormick and Tinsley 1987;Rehberg and Schafer 1968;Rooth 2011;Spreitzer and Pugh 2. For the purpose of our study, we will use the terms willpower and self-control interchangeably. The definition of willpower, according to Merriam-Webster is "the ability to control yourself."…”
Section: Literature Reviewmentioning
confidence: 99%
“…Participation in high school and college athletics has been linked to an earnings premium of between 4% and 10% (Barron, Ewing, and Waddell 2000;Cabane and Lechner 2014;Ewing 1998Ewing , 2007Lechner 2009;Lechner and Downward 2013;Lechner and Sari 2014;Long and Caudill 1991;McCormick and Tinsley 1987;Rehberg and Schafer 1968;Rooth 2011;Spreitzer and Pugh 1973;Stevenson 2010). Stevenson (2010) identified a causal link between athletic participation and greater labor force participation and higher wages among women.…”
mentioning
confidence: 99%
“…Sport participation has been studied a lot since the healthy behaviour of individuals is important not only to the participants but also to the society. Some recent summary reviews can be found in Downward et al (2014), Cabane and Lechner (2014) or Downward and Rasciute (2015).…”
Section: Relevant Literaturementioning
confidence: 99%